PENGENDALIAN MANAJEMEN PUPUK SUBSIDI - Dewi Pratiwi Indriasari; Amar Sani (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2019)
Fertilizers are a strategic means of production and play an important role in increasing productivity and production of agricultural commodities. In an effort to protect and improve the ability of farmers to implement balanced fertilization, and improve food security, the government provides fertilizer subsidies with a target of small farmers and sets the highest retail price (HET) of subsidized fertilizer. The research objectives are: for management management in subsidized fertilizer supplies. The analytical method used is multiple regression. The results of the study show that the planning, organizing, and activity variables have a significant influence on management control. The t test results obtained the better the planning, organizing, and activities provided, the better the management control. Test F also obtained results that planning, organizing, and significant activities simultaneously to management control. While the coefficient of determination R2 indicates that the value is very strong.